PENAMPILAN ENAM KULTIVAR UNGGUL KEDELAI PADA BERBAGAI JARAK TANAM YANG BERBEDA UNTUK PENANAMAN DI MUSIM HUJAN - Acep Atma Wijaya; Miftah Dieni Sukmasari (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Soybean (Glycine max L.) is one of the main commodities that become a national mainstay because it is a source of vegetable protein and is the main source of potential food after rice and corn. Efforts to meet the needs or increase food productivity in Indonesia by increasing the frequency of planting. There is no specific research on the optimal cultivar when planted during the rainy season, so it is necessary to use several cultivars and adjust the spacing in an effort to increase soybean production. The purpose of this study was to determine the effect of the interaction between cultivars and spacing, as well as the use of cultivars and spacing as what showed the best growth and yields when planted in the rainy season. The method used was Factorial RAK. With the use of cultivars Grobogan, Anjasmoro, Deja 2, Gepak Kuning, Dega 1, Dering 1, and the use of spacing of 40 cm x 20 cm and 30 cm x 30 cm. Data analysis used Duncan's multiple distance test at 5% level. Components observed from the vegetative phase to the generative phase. The results showed that the use of the Anjasmoro cultivar with a spacing of 40 cm x 20 cm was very good during the growth period, while the components of the results of the use of the yellow Gepak cultivar and the use of a spacing of 40 cm x 20 cm showed the best results.